Unusual presentation of extramedullary haematopoiesis in a young boy. Issue 3 (23rd March 2019) - Darole, Pramod; Sundar, Uma; Kuchekar, Nilesh; Karre, Ajay
Abstract : Acute transverse myelopathy in a young person may be due to infection, postinfective or inflammatory demyelination, or vascular causes. Rarely, a completely reversible cause of acute transverse myelopathy may be seen, as described here in our case of transverse myelopathy due to extramedullary haematopoiesis (EMH). An 18-year-old man who had a history of a lone blood transfusion at age of 7 years presented with paraplegia. MRI showed multiple epidural space masses of EMH compressing the spinal cord. He was detected to have thalassaemia intermedia and was treated with blood transfusions, steroids and radiotherapy to the involved paraspinal areas. He recovered fully over 15 days and remained symptom free at 6 months.